Central Vein Preservation in Critical Venous Access - Davidson, J.; Paul, A.; Patel, S.; Davenport, M.; Ade-Ajayi, N. (European Journal of Pediatric Surgery, 2016)
Introduction The lack of suitable veins in children with critical central venous access requirements is a major obstacle to optimal care and is potentially life-threatening. We present outcomes following the use of vein-preserving (VP) surgical techniques, notably the sheath exchange for tunneled lines (SETL).Materials and Methods A retrospective, single observer analysis of a prospectively maintained departmental logbook as well as the medical records of patients. Two broad groups of central line replacements were identified; those inserted following removal of a previous line and a traditional “plastic-free” (PF) period and those exchanged without such an interval.Results Overall, 19 lines were directly exchanged during the study period and compared with 34 inserted after a PF period. Similar catheter life spans and infection rates were demonstrated in each group; 125 (range, 78–173) days in VP exchanges versus 122 (range, 70–175) days in PF replacements (p = 0.41). Line Sepsis resulting in removal or change of line occurred at 103 (range, 60–147) days in VP group versus 104 (range, 45–164) days in PF (p = 0.73).Conclusion For children with critical venous access requirements, direct line exchange procedures are a robust and reproducible means of vein preservation. The outcomes compare favorably with those following the more traditional removal, a PF period and reinsertion.
Keywords: central venous access; line exchange; vein preservation; infection